Comparison of Different Extraction Methods to Predict Anthocyanin Concentration and Color Characteristics of Red Wines - Stephan Sommer; Seth D. Cohen (Fermentation, 2018)
Red wines ferment in contact with skins to extract polyphenols and anthocyanins that help build, establish, and stabilize color. Concentration and composition vary among genera, species, and cultivars. For this study, 11 grapes representing Vitis vinifera (Cabernet Sauvignon, Merlot, Cabernet Franc, Barbera, Syrah, Petite Sirah, Mourvedre), Vitis labrusca (Concord), Muscadinia rotundifolia (Noble), and French-American hybrids (Marquette, Chambourcin) were selected. All cultivars were fermented on skins while color extraction was monitored daily. Each grape was also extracted using six different methods (microwave, and ultrasound assisted, Glorie procedure, ITV Standard (Institut Technique de la Vigne et du Vin), AWRI method (Australian Wine and Research Institute), solvent extraction of skins) and compared to color characteristics of the wines produced by fermentation. Results show that the extraction pattern varies among cultivars. Post-fermentation maceration, pressing, and sulfur dioxide addition lead to color loss up to 68 percent of the original maximum with the highest loss for native American grapes and hybrid varieties. Extraction procedures over-estimate color in the finished wine but are more accurate if compared to peak extraction levels during fermentation. Color loss and suitability of different extraction procedures to predict color characteristics of fermented wine strongly depend on the complexity of the anthocyanin spectrum and therefore the cultivar used.